A passionate way of being: a qualitative study revealing the passion spiral - Susanna M. Halonen (Universidad de San Buenaventura, 2014)
Being engaged in an activity one is passionate about has been tied to feeling life is worth living for. Existing research in passion has explored this phenomenon purely using quantitative research methodology, and by tying an individual’s passion to a specific activity. In this study, passion was explored in semi-structured interviews with 12 participants. The qualitative grounded theory analysis revealed a passionate way of being, with passion being located in the individual rather than in a specific activity. A new phenomenon to positive psychology, a passionate way of being is about having a purpose, creating positive impact, and pursuing variety. These key elements, amongst others, created a reinforcing, self-sustaining spiral, which offered a route to hedonic and eudaimonic happiness, generally serving to enhance life (though it could also detract from life if it became overpowering).